A tale of two cities - Dickens, Charles, 1812-1870.; Woolsey, Kristopher (New York : Dodd Mead, 1985)
The classic novel about the French Revolution and its effect upon the lives of several individuals, both French and English.
7.9
7.9
Young Ad.-Adult.
Young Adult
Keywords: France -- History -- Revolution, 1789-1799 -- Fiction; France -- History -- 1789-1799, Revolution -- Fiction